Factors affecting the quality of mosque financial statements - Rohmatul Faizah; Ririn Irmadariyani; Agung Budi Sulistiyo (ARKA INSTITUTE, 2022)
The purpose of this study was to find out and at the same time analyze the factors that can affect the quality of the financial statements of mosques in Jember Regency. The data analysis method that the researcher uses in this research is quantitative descriptive analysis. The eight (8) hypotheses proposed by the researcher in this research were analyzed using a tool in the form of the SMART Partial Least Squares (PLS) program through two stages, namely the outer model and the inner model, before proceeding with the hypothesis testing process. Based on the results of processed SmartPLS 3.2.9 data, it can be concluded that only financial management practice variables have a significant effect on the quality of mosque financial statements, while human resource competence, internal control systems, information technology utilization, moderating effect 1 (human resource competence*organizational commitment ), moderating effect 2 (internal control system*organizational commitment), moderating effect 3 (utilization of information technology*organizational commitment), and moderating effect 4 (financial management practice*organizational commitment) showed no significant effect on the quality of financial statements in mosques in Jember Regency.